2017
DOI: 10.7717/peerj.3992
|View full text |Cite
|
Sign up to set email alerts
|

Interpopulational and seasonal variation in the chemical signals of the lizardGallotia galloti

Abstract: Communicative traits are strikingly diverse and may vary among populations of the same species. Within a population, these traits may also display seasonal variation. Chemical signals play a key role in the communication of many taxa. However, we still know far too little about chemical communication in some vertebrate groups. In lizards, only a few studies have examined interpopulational variation in the composition of chemical cues and signals and only one study has explored the seasonal effects. Here we sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
(97 reference statements)
1
7
0
Order By: Relevance
“…The seasonal differences found in this work are in line with the scarce scientific literature on seasonal variation in chemical signals of lizards [55, 61]. Specifically, we found that the most abundant compounds, squalene and cholesterol, showed higher levels in the non-reproductive season in both populations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The seasonal differences found in this work are in line with the scarce scientific literature on seasonal variation in chemical signals of lizards [55, 61]. Specifically, we found that the most abundant compounds, squalene and cholesterol, showed higher levels in the non-reproductive season in both populations.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, we found that the most abundant compounds, squalene and cholesterol, showed higher levels in the non-reproductive season in both populations. An increase in cholesterol levels in the non-reproductive season was also found in Gallotia galloti lizards [61]. Cholesterol has been proposed as a protector of other compounds with potential pheromone activity, lacking a signaling function [96].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This weakness can be explained considering that samples for the lipid study came from three distinct populations (no information are available about the site × morph frequency in the sample) over a period of two months (April to May). As both population and season can affect the composition and amount of the lipid fraction 67,90,92,117121 , potentially in a morph-specific way 43,44,122 , an unbalanced sampling of morphs by period and population could have biased results. On the opposite, the observed differences in the protein pattern cannot be imputed to population, timing, or to sampling bias, since all sampled lizards came from the same site, were collected on the same day, at the peak of the breeding season 43,86 , and the pooled secretions were obtained by balancing the contribution of each donor (see Material and Methods).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies of animal communication have primarily focused on the role that visual (trait displays) and acoustic (sounds in specific frequencies and patterns) signals play in shaping interactions, the role of chemical communication has gained an increasingly more central role in understanding the evolution of social and sexual dynamics within populations (Alberts 1992 ; Schwenk 1995 ; Martin and Lopez 2000 ; Kratochvil and Frynta 2002 ; Ibáñez et al 2017 ; MacGregor et al 2017 ). The evolution of traits responsible for chemical communication has been suggested to be driven by selection arising from competition over mates (sexual selection), and from ecological pressures that affect signal efficiency (Alberts 1992 ; Escobar et al 2001 ; Baeckens et al 2017b ; García-Roa et al 2017c ). As a result, the hypothesis that variation in the number of signalling glands is shaped by geographic gradients of climatic factors that affect the efficiency of the signal delivery, thus resulting in macroecological patterns of variation in chemical phenotypes, has been suggested (Escobar et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%